2013
DOI: 10.1177/1533317513517036
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Factors Related to College Ice Hockey Concussions

Abstract: We analyzed data from 74 male collegiate hockey players. Each athlete's season began with a baseline administration of the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) neuropsychology test battery. Fourteen athletes sustained a sport-related head injury and were readministered the test to assess the impact of the injury. A significant decrease in performance (compared to baseline) on immediate and delayed word recall and designs followed the first concussion. Following a second sport-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Nevertheless, the magnitude of the observed impairments appears similar to the one observed in collegiate hockey players who were victims of head concussion. (49) In conclusion, short-term exposure of healthy children and adolescents to an altitude at which major tourist destinations are located induced significant memory and executive deficits. These deficits are reversible after return to low altitude normoxia, but persist or even are more obvious in children permanently living at high-altitude.…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, the magnitude of the observed impairments appears similar to the one observed in collegiate hockey players who were victims of head concussion. (49) In conclusion, short-term exposure of healthy children and adolescents to an altitude at which major tourist destinations are located induced significant memory and executive deficits. These deficits are reversible after return to low altitude normoxia, but persist or even are more obvious in children permanently living at high-altitude.…”
Section: Discussionmentioning
confidence: 85%
“…37,38 Decreased visual motor speed has been seen in some subjects exposed to repetitive neurotrauma and the suggestion has been made that it may be an early indicator of progressive neurodegeneration. 39 …”
Section: Introductionmentioning
confidence: 99%
“…4,15,19,25,26,32,40,52 These findings are important because there is mounting evidence from several studies demonstrating an association between playing contact sports and sustaining concussions 7,11,32,45 and an association between repeated concussions and longterm neurological disorders. 2,8,9,12,18,20,35,36 Multiple recent studies have also found changes in neuroimaging findings, neurometabolic measurements, cerebral blood flow, brain networking, and neurocognitive domains in people with previous concussions. 3,32,44 Some of the networking and neurometabolic changes have been seen as early as adolescence, although 1 study of American football found no neurocognitive changes after 2 seasons of play in high school students.…”
Section: Discussionmentioning
confidence: 99%